Pengaruh Media Sosial, Celebrity Endorser, Brand Image, terhadap Minat Beli Ulang Pelanggan MS Glow Kupang dengan Brand Trust sebagai Variabel Intervening - Patrichia Anika Amalo; Simon Sia Niha; Henny A. Manafe; Anggraeny Paridy (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
This study aims to determine (1) respondents' perceptions of social media, celebrity endorser, brand image, repurchase intention, and brand trust, (2) the significance of social media on repurchase intention, (3) the significance of celebrity endorser on repurchase intention, (4) the significance of brand image to repurchase intention, (5) the significance of social media to brand trust, (6) the significance of celebrity endorser to brand trust, (7) the significance of brand image to brand trust, (8) the significance of brand trust to interest repurchase, (9) the significance of brand trust in mediating social media, celebrity endorsers, and brand image in influencing repurchase intention. The results of the descriptive statistical analysis make it clear that the achievement of the social media variable indicators is 69%, the achievement of the indicator variable celebrity endorser is 70%, the achievement of the indicator variable brand image is 70%, the achievement of the variable indicator of repurchase intention is 68%, and the achievement of the indicator variable brand trust is 68%. These five variables are categorized as good. The results of inferential statistics show that social media has a positive effect, but is not important enough for repurchasing interest, with a significance of 0.293 > 0.05. Celebrity endorsers have a positive and significant influence on repurchase intention, with a significance of 0.010 <0.05. Brand image has a positive and important influence on repurchase intention, its significance is 0.034 <0.05.